Exchange of supraglottic airways for endotracheal tube using the Eschmann Introducer during simulated child resuscitation: A randomized study comparing 4 devices. Issue 26 (June 2017) - Szarpak, Lukasz; Truszewski, Zenon; Vitale, Joseph; Glosser, Logan; Ruetzler, Kurt; Rodríguez-Núñez, Antonio
Abstract: Background: The aim of this study was to examine the application of the Eschmann tracheal tube introducer (ETTI) with 4 types of supraglottic airway devices (SADs) using a child-manikin. Methods: A total of 79 paramedics were asked to exchange the 4 SADs for an endotracheal tube with the ETTI in 3 different scenarios using a randomized crossover study format: normal airway without chest compression; normal airway with uninterrupted chest compression; and difficult airway with uninterrupted chest compression. The primary outcome was time to SAD exchange, with the secondary outcome measuring the success of SAD exchange. Each attempt was assessed by a trained assistant. Results: The mean exchange times for LMA, Cobra PLA, Air-Q, and SALT were as follows: 21, 23, 21, and 18, respectively for Scenario A; 23, 27, 22.5, and 21 for Scenario B; and 23, 28, 23, and 23 for Scenario C. The percent efficacy of SADs exchange with LMA, Cobra PLA, Air-Q and SALT were 98.7%, 94.9%, 100%, and 100% for scenario A; 98.7%, 88.6%, 98.7%, and 97.5% for scenario B; and 93.7%, 87.3%, 94.9%, and 93.7% for scenario C. Conclusions: In this model of pediatric resuscitation, the SAD exchange using an ETTI has (LMA, Cobra PLA, Air-Q and SALT) proved to be effective in paramedics with no previous experience. Furthermore, experimental findings indicated that SAD exchange can be achieved without interrupting chest compression.